(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2026)
Introduction. Ensuring food safety is a key task of modern food production and an important prerequisite for protecting public health. Due to the growing demand for local, traditional, and artisanal food products, craft production is actively developing; it is characterized by small production volumes, the use of local raw materials, and a significant proportion of manual processing operations. Relevance. The specific features of craft production can increase the risk of biological, chemical, and physical hazards arising during the manufacturing process. Increasing consumer demands for food quality and safety, the need to comply with national legislation and international standards, as well as the harmonization of Ukrainian regulations with European ones, necessitate the implementation of effective risk management and product safety control systems. Purpose and Objectives. The purpose of the study is to substantiate approaches to risk management and food safety control in craft production. The main objectives are to identify the primary groups of hazards, analyze the characteristics of control system organization in small enterprises, and substantiate effective risk management measures. Research Methods. The methodological framework consists of systems analysis, structural-functional analysis, hazard identification methods, logical generalization of regulatory requirements, and a comparative analysis of food safety management practices. Results. It has been established that an effective risk management system in craft production must cover all stages of the production process: incoming raw material inspection, as well as technological, sanitary-hygienic, laboratory, and logistical monitoring of process parameters. The main groups of hazards were identified: biological, chemical, physical, and allergenic. It was demonstrated that the integration of HACCP principles, prerequisite programs for production organization, and digital monitoring technologies enhances the effectiveness of critical control point management and ensures product traceability. Conclusions. A comprehensive approach to risk management contributes to improving food safety, reducing production risks, and enhancing the competitiveness of craft enterprises. The implementation of modern control systems and digital technologies fosters a culture of production safety and ensures product compliance with international standards.